Computation of feed-path based on temperature gradient method. (May 2015) - Zhou, J. X.; Zhou, Q.; Chen, T.; Yin, Y. J.; Shen, X.
<x content-type="archive" xml:space="preserve">Abstract</x> Feeding systems is an important factor for productivity and quality of casting. In this paper, the computation of feed-path based on temperature gradient method is proposed to remedy the deficiencies in the feeder optimisation through traditional numerical methods. Feed-path is the direction of microscopic flow of liquid metal during solidification. In the aspect of calculation, feed-path consists of a series of vectors in the direction of maximum temperature gradient at the evolving solid–liquid interface during the solidification process. With the help of feed-path, the feed-regions in castings can be identified, potential defects of cavity shrinkage as well as centreline porosity can be predict, and the direction and distance of feeding can be visualised intuitionally, providing reliable basis for feeder design. A typical casting is set as an example to illustrate the computation of feed-path based on temperature gradient method, and the facility of feed-path in the feeder optimisation is verified with a ladder sample.